2013
DOI: 10.3389/fonc.2013.00284
|View full text |Cite
|
Sign up to set email alerts
|

Potential Applications of Imaging and Image-Guided Radiotherapy for Brain Metastases and Glioblastoma to Improve Patient Quality of Life

Abstract: Treatment of glioblastoma multiforme (GBM) and brain metastasis remains a challenge because of the poor survival and the potential for brain damage following radiation. Despite concurrent chemotherapy and radiation dose escalation, local recurrence remains the predominant pattern of failure in GBM most likely secondary to repopulation of cancer stem cells. Even though radiotherapy is highly effective for local control of radio-resistant tumors such as melanoma and renal cell cancer, systemic disease progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 59 publications
(56 reference statements)
0
11
0
1
Order By: Relevance
“…In this study, details of the spiral proton track and the asymmetric 2D/3D dose distribution were investigated. The magnetic field not only induces the shift of Bragg-peak position as the spiral proton track, but also varies the 2D/3D dose distributions ( 11 , 12 , 14 , 15 ). Induced asymmetric variation of 2D/3D dose distributions were evaluated on the ratio of Gaussian-fit values in the 2D dose distributions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, details of the spiral proton track and the asymmetric 2D/3D dose distribution were investigated. The magnetic field not only induces the shift of Bragg-peak position as the spiral proton track, but also varies the 2D/3D dose distributions ( 11 , 12 , 14 , 15 ). Induced asymmetric variation of 2D/3D dose distributions were evaluated on the ratio of Gaussian-fit values in the 2D dose distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) systems provide good contrast of soft tissues between the tumor and organs at risk (OARs) (5)(6)(7)(8)(9); it is a prime candidate for IGPRT with several advantages over other imaging modalities. Compared to the computed tomography (CT) imaging, several studies demonstrated the advantages of MRI-based imagingguided proton radiotherapy (IGRT) (5)(6)(7)(8)(9)(10)(11)(12)(13). The MRI-IGPRT using protons can reduce uncertainties in the proton therapy process that result in lower doses to the normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the above method cannot take individual variability of brain morphology into account, and strongly depends on the somewhat subjective identification of the Bregma point. Therefore, we further improved our localization method, based on the CT-MRI fusion technique routinely applied during human deep-brain stimulation (DBS) surgeries and brain radiation therapy [22][23][24][25] . In addition to the preoperative CT, we performed a fast T 1 -weighted preoperative MRI scan directly after the CT scans.…”
Section: Resultsmentioning
confidence: 99%
“…In order to improve the efficiency of these experiments, we developed a new procedure in mice inspired by techniques used in human deep-brain surgery and brain radiation therapy [22][23][24][25] . CT imaging has been used to localize 50-µm-diameter electrodes postmortem with an accuracy sufficient for larger (>1000 µm) structures of the rat brain 26 and large (200-µm-diameter) electrodes and lesion sites were localized with CT and MRI in rats in vivo 27 .…”
mentioning
confidence: 99%
“…Since the images are acquired and fused with the reference images, translational and rotational displacements from the expected target position are calculated by software, and then errors are corrected by moving a 6D robotic couch. The quality of images is superior with kV-CBCT compared to the megavoltage imaging (26). The recent ExacTrac/Novalis 6D advanced system allows for accurate positioning comparable to invasive mask fixation (27).…”
Section: Igrtmentioning
confidence: 99%